Teaching Chaucer
XI, 167 p.
Keywords: This volume of essays offers innovations in teaching Chaucer in higher education. The projects explored in this study focus on a student-centred, active learning designed to enhance independent research skills and critical thinking. These studies also seek to establish conversations - between teachers and learners, and students and their texts.